'Big Data' informed drug development: a case for acceptability. Issue 4 (April 2021) - Desai, Neel; Edwards, A.J.; Ernest, T.B.; Tuleu, C.; Orlu, M.
Highlights: Various technologies already used by industry to collect and analyse 'Big Data'. Technologies to aid drug product approval approved by regulatory bodies. Medicines acceptability data is crucial for age-appropriate drug product approval. Acceptability data may be recorded at a several stages of drug product development. Electronic data recording may accelerate development of patient-centric medicines. Abstract : Data, which help inform various stages of drug product development, are increasingly being collected using newer, more novel platforms, such as mobile applications, and analysed computationally as much larger 'Big Data' data sets, revealing patterns relating to human behaviour and interactions. Medicine acceptability gauges the ability and willingness of patients to take their dosage forms. It has become a crucial human component of drug product design. Vouching for the age appropriateness of medicinal products, acceptability related data are now expected by regulatory bodies. Shifting from traditional paper-based to electronic data-gathering platforms will allow the pharmaceutical industry to collect real-world, real-time, clinically relevant data, capable of informing current and future drug product development, reducing time and cost, and setting foundations for patient-centric drug product design.